The Importance of Dust Distribution in Ionizing-photon Escape: NIRCam and MIRI Imaging of a Lyman Continuum-emitting Galaxy at z ∼ 3.8 - Zhiyuan Ji; Stacey Alberts; Yongda Zhu; Eros Vanzella; Mauro Giavalisco; Kevin Hainline; William M. Baker; Andrew J. Bunker; Jakob M. Helton; Jianwei Lyu; Pierluigi Rinaldi; Brant Robertson; et al. (The Astrophysical Journal Letters)
We present deep JWST/NIRCam and MIRI imaging of Ion1, a previously confirmed Lyman continuum (LyC)-emitting galaxy at z _spec  = 3.794. Together with existing Hubble Space Telescope imaging, these new observations from the JWST Advanced Deep Extragalactic Survey program enable a joint analysis of Ion1’s LyC, rest-frame UV, stellar, and dust emission with unprecedented detail. We report the first detection of dust emission at rest-frame ∼3 μ m in a high-redshift LyC-emitting galaxy using MIRI/F1500W. Our analysis suggests a porous distribution of dust in Ion1, with regions exhibiting evidence of dust deficit coinciding both with LyC-emitting regions and with the peak of H α emission. Furthermore, multiband NIRCam imaging reveals a strong far-UV-to-optical color gradient, where LyC-emitting regions appear significantly bluer than the rest of Ion1. Spatially resolved spectral energy distribution fitting confirms that this color gradient is primarily driven by spatially varying dust attenuation. Together, these findings suggest that Ion1’s LyC emission originates from a compact star-forming complex near its stellar-light centroid, where stellar feedback carves out low-H i- column-density channels, facilitating LyC escape. However, only a fraction of these LyC photons—specifically those along sightlines with minimal H i obscuration—ultimately escape and reach observers. This work underscores the critical role of dust and neutral gas geometry in shaping LyC escape in galaxies at high redshifts. Anisotropic LyC escape may be a common feature in the early Universe, which must be properly incorporated to constrain the epoch of reionization.